Influence and Relationship of Pain on Lumbar Biomechanics in a Young Adult Population with Non-Specific Low Back Pain - Sagrario Pérez-de la Cruz (MDPI AG, 2024)
The therapeutic actions indicated for low back pain, in addition to physiotherapy, include mobilization of the affected segment, as it is assumed that a loss of mobility may contribute to a patient's pain. The aim of this study was to investigate the influence of back pain on the degrees of spinal mobility in young adults. Eighty-six volunteers participated in the study. Fingertip-to-floor distance, Schöber's test, the fingertip-to-floor lateral flexion test, GHQ-12, the Fear-Avoidance Beliefs Questionnaire and the STarT Back Screening Tool were used. There were statistically significant differences between the two groups (pain and no pain) in degrees of spinal flexion (Schöber's test and side flexion) showing greater mobility in the group with pain. However, the group with low back pain showed less rotational mobility. The presence or absence of back pain had an impact on the individual's sporting practice and perception of pain, and they were able to carry out their sporting activities normally. Young adults with idiopathic low back pain showed some statistically significant differences in relation to the mobility of the spine in the different planes of movement (flexion and side flexion), conditioning their quality of life and sports practice.